RISK ASSESSMENT AND STAKEHOLDER ANALYSIS OF THE FREE NUTRITIOUS MEALS PROGRAM (MBG) FOR SCHOOL AGED CHILDREN IN INDONESIA - Septivani, Nike; Indra P, I Made; Fandayani, Enno Karina; Maulana, Wahyu (International Journal of Multidisciplinary Research and Literature, 2025)
The Program Makan Bergizi Gratis (MBG) is a nationwide initiative launched by the Indonesian government to improve children’s health and reduce malnutrition through free nutritious meals in schools. While the program is a key pillar of Indonesia’s long-term development vision (Indonesia Emas 2045), its large-scale implementation presents significant risks across operational, financial, and governance domains. This study aims to identify and assess the key risks involved in the MBG program using the ISO 31000:2018 risk management framework and a qualitative descriptive approach. Data were collected through field observations, structured interviews, stakeholder questionnaires, and document analysis involving schools, catering service providers, and student beneficiaries. Risk levels were assessed based on probability and impact ratings, and further analyzed using a risk matrix and SWOT framework. Findings reveal that schools face the highest risk exposure, particularly in areas of delayed budget disbursement, food safety, and governance transparency. Catering providers reported medium risks related to delivery logistics and hygiene standards, while students expressed concerns primarily related to meal variety and portion sizes. Three priority risk categories were identified: financial uncertainty, food quality assurance, and program accountability. This study contributes to the growing literature on public nutrition policy and risk governance by providing evidence-based recommendations to enhance program implementation. Key recommendations include digital risk monitoring platforms, improved stakeholder coordination, food safety audits, and policy transparency mechanisms. By managing these risks proactively, the MBG program can be transformed into a sustainable and equitable intervention to improve child health and education outcomes in Indonesia.